EKSISTENSI IBADAH DALAM KEHIDUPAN ORANG BERIMAN - Nonci, Muh. Hajir (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
One of the essences of da’wah is worshiping God. In line with human creation is to serve God. Operationally serving is worshiping. That is doing something as an approach to God which is commonly called worship. There are two kinds of worship, namely the KhasiSah worship and amma worship. Khassa worship is what has been required, namely (the pillars of Islam) of shahada, prayer, zakat, fasting, and pilgrimage. Whereas amma (general) worship is all actions carried out other than the compulsory above and what is clearly prohibited by God is amma worship. Therefore, everything that will be done must be accompanied by good intentions, and before being done basmalah and if the work is finished, say Hamdalah.